Association of main meal frequency and skipping with metabolic syndrome in Korean adults: a cross-sectional study - Haeun Park; Dayeon Shin; Kyung Won Lee (Nutrition Journal, 2023)
Abstract Background Reduced meal frequency can increase the risk of metabolic syndrome (MetS). However, limited studies have examined the association between meal frequency and skipping meals with MetS. This study aims to analyze the association between main meal frequency and meal skipping with MetS in Korean adults aged ≥ 19 years. Methods In this study, we included data from 22,699 Korean adult participants from the 2016–2020 Korea National Health and Nutrition Examination Survey (KNHANES). The 24-h dietary recall method was used to classify the participants into three groups based on main meal frequency (one, two, or three meals per day) and seven groups based on the type of main meal they skipped. Multivariable logistic regression analysis was conducted to determine the association between main meal frequency and the types of main meals skipped with the odds of MetS and its associated components. Appropriate estimates were accounted for using sampling weights, stratification, and clustering. Results The prevalence of MetS in the study population was 33.8%. The average age of the participants was 47.2 years with 42.6% being men, and 57.4% being women. Men who consumed two meals per day had higher odds of MetS than those who consumed three meals per day (odds ratio [OR] 1.16, 95% confidence interval [CI] 1.01–1.33). Women who consumed two meals per day, and skipped breakfast had increased odds of having elevated fasting blood glucose levels (OR 1.18, 95% CI 1.02–1.35), and elevated triglycerides (OR 1.19, 95% CI 1.02–1.39). However, women who skipped dinner had reduced odds of having elevated fasting blood glucose levels (OR 0.74, 95% CI 0.58–0.94). Conclusions Our findings suggest that meal frequency and the type of main meal skipped may be associated with MetS and emphasize the importance of consuming breakfast to prevent MetS.